2018
DOI: 10.4322/acr.2018.044
|View full text |Cite
|
Sign up to set email alerts
|

Oral focal mucinosis of the hard palate and gingiva

Abstract: Oral focal mucinosis (OFM) is an uncommon, asymptomatic, submucosal, slow-growing nodule representing a counterpart of the cutaneous focal mucinosis (CFM). OFM has a female predilection with the highest prevalence in the fifth decade of life. About 68% of OFMs occur in the gingiva and 14% in the palate. We present the case of a 41-year-old woman presenting a progressively growing mass on the palate, since the last 8 months. The diagnostic workup led to the diagnosis of an unusual OFM with the clinical presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 21 publications
3
24
1
2
Order By: Relevance
“…Since then, approximately 100 well-documented cases of OFM have been reported in the literature. [1][2][3][4][5] To the best of our knowledge, this study represents the largest series of OFM cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since then, approximately 100 well-documented cases of OFM have been reported in the literature. [1][2][3][4][5] To the best of our knowledge, this study represents the largest series of OFM cases reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to CFM, which is more prevalent in males, 2,6,38 our review of the literature showed that most oral cases affect adult women in the fourth and fifth decade of life, with a mean age of 39.1 years and 2.1:1 female-to-male ratio ( Occurrence in the retromolar region and lips ( Figure 2C-D), as observed in our series, are excessively rare, with only a few welldocumented cases published in the literature ( Table 2). The time of evolution of both entities from diagnosis to treatment is variable, ranging from some months to years.…”
Section: F I G U R E 2 Macroscopic Appearance Of Oral Focal Mucinosismentioning
confidence: 91%
See 3 more Smart Citations